2015
DOI: 10.1155/2015/451405
|View full text |Cite
|
Sign up to set email alerts
|

Lipoamino Acid Coated Superparamagnetic Iron Oxide Nanoparticles Concentration and Time Dependently Enhanced Growth of Human Hepatocarcinoma Cell Line (Hep‐G2)

Abstract: Superparamagnetic iron oxide nanoparticles (SPION) have been widely used in medicine for magnetic resonance imaging, hyperthermia, and drug delivery applications. The effect of SPION on animal cells has been a controversial issue on which there are many contradictions. This study focused on preparation of SPION with novel biocompatible coatings, their characterization, and cytotoxicity evaluation. An amino acid (glycine) and two novel lipo-amino acids (2 amino-hexanoic acid and 2 amino-hexadecanoic acid) coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 43 publications
4
60
0
1
Order By: Relevance
“…X-ray powder diffraction (XRD, Siemens D5000) analysis was done to determine the crystallinity of prepared AgNPs. Functional groups of the phytochemicals which coat the prepared nanoparticles were determined by Fourier transformed infrared spectroscopy (Bruker, Vertex 70, FTIR Spectrometer) (Ebrahiminezhad et al, 2013;Gholami et al, 2015).…”
Section: Characterization Of Silver Nanoparticlesmentioning
confidence: 99%
“…X-ray powder diffraction (XRD, Siemens D5000) analysis was done to determine the crystallinity of prepared AgNPs. Functional groups of the phytochemicals which coat the prepared nanoparticles were determined by Fourier transformed infrared spectroscopy (Bruker, Vertex 70, FTIR Spectrometer) (Ebrahiminezhad et al, 2013;Gholami et al, 2015).…”
Section: Characterization Of Silver Nanoparticlesmentioning
confidence: 99%
“…Many of the previous studies revealed that IONs can interrupt the integrity of cell membrane and adversely affect normal cell functionalities (Berry et al 2004;Liu et al 2004;Can et al 2009). Contrary, some studies have reported that IONs at certain concentrations show no negative toxic or inhibitory effects on some microbial cells and also there are growth stimulatory effects (Grumezescu et al 2010;Ficai et al 2012;Islam et al 2012;Gholami et al 2015). By reviewing the literature, it seems that the effect of IONs on the growth and metabolic profile of microorganisms depends on the cell type.…”
Section: Introductionmentioning
confidence: 99%
“…. FeO characteristic peak of Fe‐EPS appeared at 555 cm −1 which indicates the presence of iron oxide‐hydroxide nanoparticles . The CO and CC stretching vibration peaks were observed at 1027 and 1403 cm −1 respectively.…”
Section: Resultsmentioning
confidence: 96%